Use of Autologous Cord Blood Mononuclear Cells Infusion for the Prevention of Bronchopulmonary Dysplasia in Extremely Preterm Neonates: A Study Protocol for a Placebo-Controlled Randomized Multicenter Trial [NCT04440670] - Ren, Zhuxiao; Fang, Xu; Zhang, Qi; Mai, Y. G.; Tang, X. Y.; Wang, Q. Q.; Lai, C. H.; Mo, W. H.; Dai, Y. H.; Meng, Q.; Wu, Jing; Ao, Z. Z.; et al. (Frontiers in Pediatrics, 2020)
Background: Despite the rapid advance of neonatal care, bronchopulmonary dysplasia (BPD) remains a significant burden for the preterm population, and there is a lack of effective intervention. Stem cell depletion because of preterm birth is regarded as one of the underlying pathological mechanisms for the arrest of alveolar and vascular development. Preclinical and small-sample clinical studies have proven the efficacy and safety of stem cells in treating and preventing lung injury. However, there are currently no randomized clinical trials (RCTs) investigating the use of autologous cord blood mononuclear cells (ACBMNC) for the prevention of BPD in premature infants. The purpose of this study is to investigate the effects of infusion of ACBMNC for the prevention of BPD in preterm neonates less than 28 weeks. Methods: In this prospective, randomized controlled double-blind multi-center clinical trial, 200 preterm neonates less than 28 weeks gestation will be randomly assigned to receive intravenous ACBMNC infusion (5×107 cells/kg) or placebo (normal saline) within 24 hours after birth in a 1:1 ratio using a central randomization system. The primary outcome will be survival without BPD at 36 weeks of postmenstrual age or at discharge, whichever comes first. The secondary outcomes will include the mortality rate, other common preterm complication rates, respiratory support duration, length and cost of hospitalization, and long-term outcomes after a 2-year follow-up. Conclusion: This will be the first randomized, controlled, blinded trial to evaluate the efficacy of ACBMNC infusion as a prevention therapy for BPD. The results of this trial will provide valuable clinical evidence for recommendations on the management of BPD in extremely preterm infants.